A Reader's Guide to Nabokov's "Lolita" - Connolly, Julian W. (Studies in Russian and Slavic Literatures, Cultures, and History, 2009)
One of the most fascinating and controversial novels of the twentieth century, Vladimir Nabokov's Lolita is renowned for its innovative style and notorious for its subject matter and influence on popular culture. The book guides readers through the intricacies of Nabokov's work and helps them achieve a better understanding of his rich artistic design. The book opens with a detailed chronology of Nabokov's life and literary career. Chapters include an analysis of the novel, a discussion of its precursors in Nabokov's work and in world literature, an essay on the character of Dolly Haze (Humbert's "Lolita"), and a commentary on the critical and cultural afterlife of the novel. The volume concludes with an annotated bibliography of selected critical reading. The guide should prove illuminating both for first-time readers of Lolita and for experienced re-readers of Nabokov's text.